Rethinking the Influence of Chloroplast Movements on Non-photochemical Quenching and Photoprotection. Issue 3 (13th May 2020) - Wilson, Sam; Ruban, Alexander V.
Abstract : Chloroplast movement-related optical alterations in plant cell ultrastructure do not impact non-photochemical quenching nor act as a photoprotective mechanism. Abstract: Under blue light, plant chloroplasts relocate to different areas of the cell. The photoreceptor phototropin2 (phot2) mediates the chloroplast movement mechanism under excess blue light alongside the chloroplast unusual positioning1 (chup1) protein. Recently, it has been proposed that leaf transmittance changes associated with chloroplast relocation affect measurements of nonphotochemical quenching ( NPQ ), resulting in kinetic differences due to these movements (termed "qM"). We evaluated these claims using Arabidopsis ( Arabidopsis thaliana ) knock-out mutants lacking either phot2 or chup1 and analyzed the kinetics of both the onset and recovery of NPQ under equivalent intensities of both red and blue light. We also evaluated the photoprotective ability of chloroplast movements both during the early onset of photoinhibition and under sustained excess light. We monitored photoinhibition using the chlorophyll fluorescence parameter of photochemical quenching in the dark, which measures the redox state of QA within PSII without any of the complications of traditional F v / F m measurements. While there were noticeable differences between the responses under red and blue light, the chloroplast movement mechanism had no effect on the rate or amplitude of NPQ onset or recovery. Therefore, we were unable to replicate the "qM" component and its corresponding influence on the kinetics of NPQ in Arabidopsis grown under "shade" conditions. Furthermore, chloroplast relocation had no effect on the high-light tolerance of these plants. These data cast doubt upon the existence of a chloroplast movement-dependent component of NPQ . Therefore, the influence of chloroplast movements on photoprotection should be thoroughly reevaluated.